2020
DOI: 10.1177/0969141320914323
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of gynaecological check-up and their association with body mass index within the CONSTANCES cohort

Abstract: Objectives To investigate the relationship between patterns of gynaecological check-up and body mass index while accounting for various determinants of health care use. Methods Sequence analysis and clustering were used to highlight patterns of gynaecological check-up, which included the regularity of breast and cervical cancer screening and visits to the gynaecologist over four years, among 6182 women aged 54–65 included in the CONSTANCES cohort between 2013 and 2015 in France. Multinomial logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Women living with severe obesity were most likely to have a cervical smear following a referral to screening by a doctor 27 . Women living with obesity were found to be less likely to routinely visit a gynecologist, and even when they did, they were less likely to be screened for cervical cancer than normal weight women 20 . Physician recommendation for screening was also found to be a key factor in colorectal cancer screening uptake among both women living with obesity and women with overweight or normal body mass index 23, 26 and among men living with obesity 26 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Women living with severe obesity were most likely to have a cervical smear following a referral to screening by a doctor 27 . Women living with obesity were found to be less likely to routinely visit a gynecologist, and even when they did, they were less likely to be screened for cervical cancer than normal weight women 20 . Physician recommendation for screening was also found to be a key factor in colorectal cancer screening uptake among both women living with obesity and women with overweight or normal body mass index 23, 26 and among men living with obesity 26 .…”
Section: Resultsmentioning
confidence: 99%
“…27 Women living with obesity were found to be less likely to routinely visit a gynecologist, and even when they did, they were less likely to be screened for cervical cancer than normal weight women. 20 Physician recommendation for screening was also found to be a key factor in colorectal cancer screening uptake among both women living with obesity and women with overweight or normal body mass index 23,26 and among men living with obesity. 26 A smaller number of men and women with obesity reported a physician recommendation for colorectal cancer screening than those who were overweight or normal weight.…”
Section: Screening Uptake and Risk Awarenessmentioning
confidence: 96%
See 1 more Smart Citation
“…Our results are consistent with those of Franck et al, who have reported that women with obesity have low rates of cervical cancer screening. Limited health literacy and social deprivation have been associated with suboptimal screening as well (25,26). Because individuals from class III have a higher prevalence of vulnerability and social deprivation indicators, the decrease in the use of gynecological care could have important consequences for this specific population.…”
Section: Discussionmentioning
confidence: 99%
“…Because absolute risk of developing a gynecological cancer has been shown to be higher in women with obesity, a weaker access to screening for women with severe obesity further increases their mortality risk (23,24) be a targeted goal of public health policy, and specific interventions could reduce inequities and prevent them from compromising their health (26,27).…”
Section: Discussionmentioning
confidence: 99%